HUBUNGAN KUALITAS PELAYANAN KADER DENGAN KEPATUHAN KUNJUNGAN IBU YANG MEMILIKI BALITA KE POSYANDU DI DESA SARILABA JAHE KECAMATAN BIRU-BIRU KABUPATEN DELI SERDANG TAHUN 2022 - efrata sembiring; Sri Sudewi Pratiwi Sitio; Yunita Syahputri Damanik; Muhammad Rifqi Azhary; Nada Amirah (Jurnal Penelitian Kesmasy, 2023)
A healthy society is realized if there is awareness of every member of the community about the importance of healthy behavior, desire, and empowerment to live a healthy life. One of the efforts to empower the community is by conducting posyandu activities. One of the causes of the decline in service satisfaction and visits at the posyandu is due to the low skills of cadres. The purpose of this study was to determine the relationship between cadre service quality and adherence to visits by mothers with toddlers to the posyandu in Sarilaba Jahe Village, Biru-Biru District, Deli Serdang Regency in 2022. This type of research used quantitative research with a cross sectional design. Data analysis was carried out univariately and bivariately using the chi square test with a sample of 48 mothers with toddlers who were taken randomly using simple random sampling. The results of the bivariate analysis with the chi square test obtained the value of tangible service quality (sig P = 0.002 < 0.05), reliability (sig P = 0.001 < 0.05), responsiveness (sig P = 0.001 < 0.05) , assurance (sig P = 0.002 < 0.05) and empathy (sig P = 0.002 < 0.05) indicate that there is a relationship between cadre service quality and compliance with visits by mothers who have toddlers to posyandu in Sarilaba Jahe Village, Biru-Biru District. Deli Serdang Regency in 2022. Suggestions for cadres to always provide knowledge, understanding and health education about the importance of Posyandu for toddlers so that there is motivation for mothers of toddlers to visit Posyandu.